PENGARUH ENERGI AKTIVASI TERHADAP AKTIVITAS NANOPARTIKEL ZnFe2O4 PADA ADVANCED OXIDATION PROCESSES (AOPs) SEBAGAI PENGURAI RHODAMINE B - Kadarisman, Kadarisman; Nurhasanah, Iis (BERKALA FISIKA, 2021)
Advanced Oxidation Processes (AOPs) is one of the methods used to treat organic dye waste. Powder-based AOPs as photocatalyst have disadvantages due to surface adsorption and agglomeration, thereby reducing the percentage of dye decomposition. In this study, the addition of chemical energy (photo-Fenton-like) and ultrasonic waves (sono-photocatalyst) in the photocatalyst process was used to increase the activity of powder-based photocatalyst material as a decomposer of Rhodamine B organic dye. The photocatalyst material used was ZnFe2O4 nanoparticles synthesized using precipitation method with a calcination temperature of 700oC for 3 hours. The combination of light energy (4.69 eV) and chemical energy (44 meV) in the photo- Fenton-like process showed the highest percentage of Rhodamine B decomposition (70%). The use of ultrasonic energy (28 meV) in the sono-photocatalyst process increases the rate of decomposition of RhB by 2 times. The addition of chemical energy (44 meV) increased the photocatalyst activity of ZnFe2O4 nanoparticles on decomposition of RhB by 8 times. The results showed that the addition of chemical energy to the photocatalyst activity of ZnFe2O4 was much more efficient than the addition of ultrasonic energy.